Business and community in Medieval England : the Cambridge Hundred Rolls source volume - Casson, Catherine; Casson, Mark, 1945-; Lee, John S.; Phillips, Katie (Bristol : Bristol University Press, 2020)
One of the most important manuscripts surviving from thirteenth-century England, the corpus of documents known as the Hundred Rolls for Cambridge have been incomplete until the recent discovery of an additional roll. This invaluable volume replaces the previous inaccurate transcription by the record commission of 1818 and provides new translations and additional appendices. Shedding new light on important facets of business activity in thirteenth-century Cambridge, this volume makes a significant contribution to our knowledge of the early phases of capitalism. This unique text will be of interest to anyone working in the fields of economic and business history, entrepreneurship, philanthropy and medieval studies. A research monograph based on recently discovered historical documents, Compassionate Capitalism: Business and Community in Medieval England, by Casson et al, is also now available from Bristol University Press.
Title from publisher's bibliographic system (viewed on 19 Mar 2021).
Keywords: Industries -- Social aspects -- England -- History; England -- Commerce -- History -- To 1500.; England -- Economic conditions -- 1066-1485.; England -- Social conditions -- 1066-1485.